ANALISIS KELAYAKAN INVESTASI KAPAL KHUSUS ANGKUTAN TERNAK DI INDONESIA SKENARIO RUTE CELUKAN BAWANG-TANJUNG PRIOK-CIREBON - Titik Triary Wijaksani; Rita Nurmalina; Burhanuddin Burhanuddin (Forum Agribisnis, 2018)
Government had made the first livestock vessel investment in Indonesia, namely KM Camara Nusantara I (KM CN I) which was operationalizing since 2016. The livestock vessel supported beef cattle distribution from East Nusa Tenggara Province (NTT) to DKI Jakarta Province by route Tenau-Waingapu-Tanjung Priok-Cirebon. In addition the government makes another new 5 livestock vessels investment which is one of them planned for beef cattle distribution from Bali Province by Celukan Bawang Port to DKI Jakarta Province by Tanjung Priok Port. Livestock vessel investment required high cost up to Rp 58 billion per unit. Moreover the operational of KM CN I still subsidized by the government.  Therefore the objective of this study is to analyze livestock vessel investment by route scenario Celukan Bawang-Tanjung Priok-Cirebon on nonfinancial aspect, financial, economic and sensitivity analyses. Nonfinancial aspect analysis used descriptive method. Financial and economic analyses used Cost and Benefit Analysis (CBA), with shadow price for economic analysis. Sensitivity analysis used switching value method. Nonfinancial aspect analysis indicated the investment feasible. Financial analysis for livestock vessel return scenario to Celukan Bawang Port without cargo and carrying feed cargo are not feasible (NPV<0). Economic analysis for return scenario without cargo is not feasible (NPV<0), meanwhile for return scenario by carrying feed cargo is feasible (NPV>0, B/C Ratio>1, IRR 5.70% higher than discount rate, and Payback Period 13.84 years). Sensitivity analysis indicated the investment is feasible by minimum increase in the price of ticket fare 534.56% for return scenario without cargo and 410.12% by carrying feed cargo.